2003
DOI: 10.1089/109493103322011515
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety in Virtual Environments: Results of a Pilot Study

Abstract: This paper reports on a pilot study of the extent to which social anxiety can be generated within a virtual environment. Ten subjects were exposed to a virtual reality experience depicting a London underground train and also a wine bar. The first provided a social setting with virtual characters (avatars) that had relatively neutral behaviors towards the subject, and the second was more socially demanding--with subjects required to interact with relatively disinterested avatars. The purpose was to assess wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…This suggests two things: first, that the environments trigger emotionally significant responses in high test anxiety students; second, that these responses are not caused merely by the use of virtual reality, since the low test anxiety students showed lower symptoms of anxiety or depression during exposure. These results are consistent with those of other validation studies of virtual environments, in which virtual reality proved effective in producing anxiety responses in subjects with higher scores on fear of public speaking (Pertaub, Slater, & Barker, 2002;Slater et al, 2006), students exposed to socially demanding situations (James et al, 2003), patients with other specific phobias (Robillard et al, 2003), and patients with eating disorders (Gutiérrez-Maldonado et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests two things: first, that the environments trigger emotionally significant responses in high test anxiety students; second, that these responses are not caused merely by the use of virtual reality, since the low test anxiety students showed lower symptoms of anxiety or depression during exposure. These results are consistent with those of other validation studies of virtual environments, in which virtual reality proved effective in producing anxiety responses in subjects with higher scores on fear of public speaking (Pertaub, Slater, & Barker, 2002;Slater et al, 2006), students exposed to socially demanding situations (James et al, 2003), patients with other specific phobias (Robillard et al, 2003), and patients with eating disorders (Gutiérrez-Maldonado et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…However, there is a growing body of experimental data allowing to interpret these results. For example, James et al 27 have immersed 10 non-phobics in various virtual social environments and found an increase in anxiety when users had to interact with virtual humans who appeared disinterested to the presence of the participants. Later on, the same research team 41 compared the reaction of 16 phobics and 20 non-phobics when they gave a speech in one of two conditions: an empty seminar room, or to a group of virtual humans behaving neutrally.…”
Section: Resultsmentioning
confidence: 99%
“…Based on clinical observations and comparisons with other published outcome studies, the treatment was considered effective. Other research teams are also working on VR treatment designed specifically for social phobias, 26,27 but outcome data have not been reported yet.…”
mentioning
confidence: 99%
“…Other studies have already shown the capacity of VR to elicit states of anxiety in patients with other pathologies. [22][23][24] …”
Section: Discussionmentioning
confidence: 99%